(untitled) (ENTHYMEMA, 2017)
In this paper, Remo Ceserani reflects upon the notions of canon and anthology in relation to the institutions behind them. After a short premise in which the traditional role of Church and school in the process of canonization is taken into account, the discussion moves to the present age, focusing on the idea of canon that lies at the basis of both North-American and Italian anthologies. In the former case, Ceserani highlights how the emergence of world literature has led to revise the structure of anthologies; in the latter case, the author argues that the canon mutuated from the work of Francesco De Sanctis still functions as the main source for many anthologies. He then concludes by stating that a thematical approach could constitute an alternative structuring criterion for a scholastic anthology.